Primary School Students’ Perception of Inspectors and Inspection Period in Turkey - Gökçe, Asiye Toker; Kantos, Züleyha Ertan (Mediterranean Journal of Social Sciences, 2012)
School inspection is essential for the educational achievements, and educators are inspected year at schools every academicin Turkey. Students are also affected by the inspection process while their teachers are examined by inspectors at class time. This studyaimed to address primary school inspectors through the perceptions of the students, whose teachers were inspected during a class time.A 16-item open ended question form, which was developed by the authors, was conducted for the 60 5th-grade students who inspected.The data gathered were analyzed through qualitative methods. The data suggest that inspectors’ manner such as shouting, being angry,humiliating, scowling, being serious, controlling and taking notes, staring the students, and carrying and playing ruler in his/her handsfrightened the students. Besides, the students liked inspectors who were friendly, kind, natty and well-dressed, and who made jokes, andused good communication skills. The results of the study are supposed to foster the essence of school inspection and, in consequence,quality of education.